Influence of the anthropogenic factor to the water quality of the tributaries and the littoral zone of Lake Ohrid - Lokoska, Lenče; Novevska, Vera (Macedonian Journal of Ecology and Environment, 1997)
In this paper are presented results of the microbiological investigations of the tributaries (Sateska, Koselska, Velgoska and Cerava) and the littoral zone of Lake Ohrid during 1996/97. Here are included the quantities of saprophytic and coliform bacteria, presence and numbers of the Escherichia coli and Clostridium perfringens and the biodegradable organic matter in the water as well. According to the obtained data, categorization of the water sensu Kohl (1975), Tumpling (1969) and Kavka (1994) was done.